Four social psychological lenses for developmental psychology - Zittoun, Tania; Perret-Clermont, Anne-Nelly (My University, 2009)
Comment intégrer les progrès de la psychologie et de la psychologie du développement? Cet article théorique propose d’examiner quatre modèles utilisés dans la tradition post-piagétienne pour étudier le développement et l’apprentissage dans leur situation sociale: le triangle psychosocial, le cadre, l’idée de transfert ou de transition, et les modèles intégrant l’idée d’outil culturel. Nous montrons les dynamiques que les travaux utilisant ces modèles ont pu mettre en évidence. Nous discutons finalement les notions même de développement et de personne qui se dégagent de ces approches., How can the advances of social and developmental psychology be integrated? This conceptual paper proposes to examine four basic theoretical models of social situations through which learning and development have been observed in the post-piagetian tradition: the psychosocial triangle, the frame, models of transfer and transitions, and models integrating the notion of cultural instrument. We show different dynamics highlighted by series of studies using these models. We finally discuss the notions of development and of the person emerging through such social developmental approaches.
Keywords: Cultural instrument; Development; Frame; Model; Psychosocial triangle; Transition